MENAKAR URGENSI KEBIJAKAN DIGITALISASI PESANTREN: ANTARA MODERNITAS DAN PENJAGAAN TRADISI - Kholid, Muhammad Idham; Muhammad; Edy Muhammad Jayadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Digitalization of Islamic boarding schools (pesantren) is a strategic phenomenon in responding to the dynamics of modernity and the transformation of education in the digital era. This study aims to assess the urgency of pesantren digitalization policies and analyze the dialectical relationship between the demands of modernity and efforts to preserve tradition. The method employed is a qualitative literature study through the analysis of various relevant scholarly sources. The findings indicate that the digitalization of pesantren has become a structural necessity for enhancing the competitiveness of Islamic educational institutions amid globalization and technological advancement. Digitalization serves as an important instrument for improving the quality of students' education, particularly by expanding access to learning resources, encouraging instructional innovation, and developing digital literacy competencies. However, the implementation of digitalization is not free from dilemmas between modernization and the preservation of traditional pesantren values, especially concerning the kiai–santri relationship, the internalization of ethical conduct (adab), and scholarly authority. Furthermore, several challenges hinder its implementation, including limited infrastructure, inadequate digital competencies among human resources, and cultural resistance within pesantren communities. Therefore, an integrative model is needed to harmonize digital technology with traditional values through a value-based approach. This model positions digitalization as a supporting instrument rather than a substitute, thereby creating a balance between innovation and the preservation of pesantren identity. Consequently, policies on pesantren digitalization should be designed in a contextual, adaptive, and sustainable manner while remaining oriented toward the preservation of Islamic values.